USE OF INNOVATIVE METHODS IN TEACHING A FOREIGN LANGUAGE - Isroilova Tursuntosh (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article highlights the importance attached to foreign languages in the Republic of Uzbekistan and the innovative technologies needed to study them.